Syngas production from glycerol dry reforming using Nd2RuO5 perovskite catalysts - Malek, Ahmad Faiz; Rosli, Siti Nor Amira; Roslan, Nurul Asmawati; Mohd-Nasir, Nor Shafiqah; Lian, William Mah Wey; Mohd Razali, Nur Aqilah; Osazuwa, Osarieme Uyi; Zainal Abidin, Sumaiya (AIP Publishing, 2022)
Currently, fossil fuels as the global energy sources have become a liability due to the emission of greenhouse gases that causes global temperature elevated and climate changes to happen more frequently. As a result, glycerol dry reforming (GDR) has been a research priority, owing to its reforming capabilities in turning greenhouse gases (CO2) and biodiesel byproducts (glycerol) into syngas. The choice of catalysts is critical for increasing the efficiency of the syngas production process. Hence, this paper studies the application of Nd2RuO5 perovskite catalysts on the dry reforming of glycerol. Before characterization, the catalysts were prepared by using the Pechini Sol-Gel method. GDR reactions were conducted using a fixed-bed reactor at operating conditions; 873 – 1173 K and CO2 to Glycerol ratio (CGR) at 1:1. Based on XRD finding, the dominant phase belongs to Nd2RuO5, a pseudo double perovskite. The reduction profile from TPR showed a lowered reduction temperature which belongs to Ru that reduced into Ru0. The images of perovskite showed a well dispersed and smooth surface, and no agglomeration occurred on the pore sites. From the catalytic evaluation on the effect of temperature, the best temperature was observed at 1073 K, giving the highest glycerol conversion at 69%, whereas for H2, CO yields 20.8% and 13.8%, respectively. Intense carbon formation has been detected at post XRD analysis which later confirmed to be a filamentous type, that oxidized at low oxidation temperature from 400 – 500 K.